The Influence of Work Shifts and Work Stress on Employee Performance at the Alfamart Kotabumi Branch, North Lampung - Santika, Wulan; Fitrianita, Siska; F Sanjaya, Vicky (Terbuka Journal of Economics and Business, 2021)
The results of the interview above show that the work shift factor gets the highest position, which is as many as 13 answers. Then, the second position is work stress as many as 8 answers and it is concluded that the factors that have a major influence on employee performance are work shifts and work stress. To strengthen indications of declining employee performance, the authors conducted interviews with 15 employees. These interviews were conducted with employees and the results could be more objective. Interviews were conducted to determine the factors that influence the decline in employee performance. Of the 15 employees, each answered 2 answers regarding the factors that decreased employee performance.